Motherhood dalam Novel Chanson Douce Karya Leila Slimani: Analisis Dekonstruksi Derrida - Anjani, Albertine Darasita; Udasmoro, Wening; Firmonasari, Aprillia (Sasdaya: Gadjah Mada Journal of Humanities, 2022)
Motherhood ideology is commonly found in literary works, including narratives depicting the figure of a mother. In literature, especially in Europe, the figure of a mother is mystified and is often associated with the figure of the Virgin Mary. This is closely related to the oppression experienced by women due to the inequality of gender construction produced by society. The novel Chanson Douce by Leila Slimani narrates two mothers with different backgrounds. This study aims to carry out a deconstruction reading, especially on the discourse of motherhood. In interpreting something we are always dominated by dominant hierarchies and superior poles which are considered as "single truth". This single truth can lead to vulnerability to discrimination or service. The deconstruction method used in this study uses the concepts of trace and difference, in readings that lead to the meaning of texts that are "friendly" to the others. The results of this study lead us to new questions regarding the challenges of motherhood in this post-industrial era.